HUMAN QUALITY INDEX MEASUREMENT; A LITTERATEUR REVIEW - Syaiful Anwar; Nasri Bachtiar; Sri Maryati; Edi Arianto (International Journal of Social Science, 2024)
The measurement of human well-being and progress has long been a subject of interest across various disciplines. In the realm of economics, the Human Quality Index (HQI) emerges as a crucial metric for assessing the overall welfare and development of societies. This literature review delves into the conceptualization, methodologies, and applications of HQI, primarily from the perspective of economics theories. The HQI encompasses a multidimensional approach, capturing various aspects of human life beyond economic indicators. Drawing from the capabilities approach pioneered by Amartya Sen, HQI considers not only income but also factors such as health, education, environmental quality, and social inclusion. By acknowledging the intrinsic value of human capabilities, HQI offers a more comprehensive understanding of societal progress, aligning with the broader goals of sustainable development. Methodologically, HQI measurement involves the aggregation of diverse indicators into a single index, often through weighted averages or composite scoring systems. While this approach enables a holistic assessment, it also poses challenges regarding data availability, comparability, and subjective weighting. Furthermore, the choice of indicators and their respective weights can significantly influence the final HQI scores, highlighting the importance of transparency and stakeholder engagement in the measurement process. The literature reveals a plethora of applications for HQI, ranging from policy evaluation to international comparisons and advocacy efforts. At the national level, HQI serves as a tool for policymakers to monitor progress, identify areas for intervention, and prioritize resource allocation. Internationally, HQI facilitates cross-country comparisons, fostering peer learning and collaboration towards common development goals. Moreover, HQI advocacy efforts aim to raise awareness about human well-being beyond economic growth, advocating for policies that enhance quality of life and social justice. Despite its utility, HQI faces several critiques and methodological debates. Critics argue that HQI oversimplifies complex realities, neglects cultural differences, and imposes Western-centric notions of development. Methodologically, concerns arise regarding data reliability, indicator selection bias, and the treatment of interdependencies among dimensions. Addressing these challenges requires ongoing research, innovation, and collaboration across disciplines to refine HQI methodologies and ensure their relevance and robustness in diverse contexts.In conclusion, the Human Quality Index represents a significant advancement in measuring human well-being and progress from an economics perspective. By integrating multiple dimensions of human life and capabilities, HQI offers a more nuanced and holistic understanding of societal development. However, ongoing efforts are needed to address methodological challenges, enhance data quality, and promote inclusivity in HQI frameworks to ensure their effectiveness and relevance in guiding policy and fostering sustainable human development